Dilution Dependent of Different Types of Redispersing Oils on Magnetorheological Greases - Mohamad, Norzilawati; Yasser Abd Fatah, Abdul; Amri Mazlan, Saiful; Azmah Nordin, Nur; Nabil Muhtazaruddin, Mohd; Fitri Mohd Yakub, Mohd (International Journal of Engineering and Technology, 2019)
This paper presents the influence of percentages of different types of oils as additives used in controlling the initial apparent viscosity of the magnetorheological (MR) grease without the occurrence of sedimentation. A series of MR greases without and with different types of oils (castor oil and silicone oil) as additives were prepared in the same weight fractions of carbonyl iron (CI) particles for comparison purpose. The rheological test was performed using shear rheometer using rotational mode under the variation of magnetic fields at constant room temperature. It was observed that initial viscosity of MR grease is reduced with increasing weight percentages of castor oil. In contrast, initial viscosity of the MR grease incorporated of silicone oil increased as the weight percentages are increased. The same trend is examined for both types of oils in off- and on-state condition. This indicates that the structuration of the magnetizable particles in the grease medium is affected by addition of different types of oils, indirectly improved the MR greases properties which applicable for industrial applications. Â Â